If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44(x + 53) = 54(52 + -9x) Reorder the terms: 44(53 + x) = 54(52 + -9x) (53 * 44 + x * 44) = 54(52 + -9x) (2332 + 44x) = 54(52 + -9x) 2332 + 44x = (52 * 54 + -9x * 54) 2332 + 44x = (2808 + -486x) Solving 2332 + 44x = 2808 + -486x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '486x' to each side of the equation. 2332 + 44x + 486x = 2808 + -486x + 486x Combine like terms: 44x + 486x = 530x 2332 + 530x = 2808 + -486x + 486x Combine like terms: -486x + 486x = 0 2332 + 530x = 2808 + 0 2332 + 530x = 2808 Add '-2332' to each side of the equation. 2332 + -2332 + 530x = 2808 + -2332 Combine like terms: 2332 + -2332 = 0 0 + 530x = 2808 + -2332 530x = 2808 + -2332 Combine like terms: 2808 + -2332 = 476 530x = 476 Divide each side by '530'. x = 0.8981132075 Simplifying x = 0.8981132075
| 4x+-1=5x+1 | | f(x)=5x^2-35 | | A^2+16=-10a | | X=4.95 | | 7z=3z-20 | | 19-8,2x=19 | | -8x-13=-5x-19 | | 1/3a-1/2a=1/2-1 | | h=-16t^2+80 | | 48=2x+3x-7 | | 10+3log(2x)=16 | | 1/3a-1/2a=-1 | | 6x-7x=-26 | | 6x-18=9x+4 | | 4x-2=17-x | | 18=5c | | https://onslow.powerschool.com/guardian/home.html | | -y/6=-8/9 | | (3b-2)/3=(b-2)/6 | | f(1)=3x+-8 | | R/3=1/2 | | 3t=8-t | | s/4=10 | | 14+2y-3+7x-12y+3x-20= | | 3x-10/2=2y | | 7+77=44x+25 | | 60=bh | | (2x^2+1)(4x-2)= | | n/49=9 | | -5x+8y=-3 | | 5/4*2 | | -10+5X=-40 |